The touristic Porto: gazing over the city - Miranda,Tiago (2018)
This article is the outcome of a research in Sociology about tourism in the city of Porto in the year of 2015, viewed through the emerging city break modes of travel. We endeavored to understand, through the foreign tourists' gazes as well as from images that shape the city as touristic, whether Porto was an authentic city, unlike any other, in the context of rampant growth tourism has seen there and in Portugal during the first two decades of the twenty-first century, subject to a larger European circuit. The most relevant conclusions point toward the touristic and global turn of Porto, with ever-growing visitors, and grappling with potentially nefarious effects derived therefrom; but keeping - in the eyes of the foreign tourist who visits it - its authenticity, unique in its own way, and in the distinct way of each one who experiences and beholds this city.